Biochemical, Nutritional, and Sensory Quality of the Low Salt Fermented Shrimp Paste. Issue 6 (3rd July 2017) - Cai, Luyun; Wang, Qingjun; Dong, Zhijian; Liu, Shucheng; Zhang, Chaohua; Li, Jianrong
ABSTRACT: Changes in the biochemical, nutritional, and sensory properties of the low salt fermented shrimp paste during fermentation were studied. The total volatile base nitrogen (TVB-N) content and total viable counts significantly increased. The pH value significantly decreased, while thiobarbituric acid (TBA) content significantly increased over 14 days. The lightness ( L* ) value significantly decreased during the initial 7 days of fermentation and significantly increased thereafter. The redness ( a* ) and yellowness ( b* ) values and astaxanthin content of the low salt fermented shrimp paste gradually increased during the 30 days of fermentation. C16:0, C18:0, C18:1n9t, C20:1n7c, C20:5n3, and C22:6n3 were the predominant fatty acids, while aspartate, glutamate, alanine, leucine, lysine, arginine, and proline were the predominant amino acids in the shrimp paste. N-containing compounds, such as pyrazine, comprised the majority of the volatile compounds. The results obtained from quantitative descriptive analysis showed that low salt fermentation can improve the flavor of the shrimp paste and is, therefore, a promising method to industrially prepare the shrimp paste.